Where are the males? The influence of bottom-up and top-down factors and sociability on the spatial distribution of a territorial ungulate - Panebianco, Antonella; Gregorio, Pablo Francisco; Schroeder, Natalia; Marozzi, Antonela Alejandra; Ovejero Aguilar, Ramiro Jose Antonio; Heidel, Lara; Peña, Fiama; Leggieri, Leonardo Ramón; Taraborelli, Paula Andrea; Carmanchahi, Pablo Daniel (Springer, 2022)
The factors that regulate the abundance and distribution of wild herbivores are key components of a species’ ecology and include bottom-up and top-down mechanisms, as well as aspects related to social organization. In territorial ungulates, males distribute themselves to enhance access to females by anticipating how resources will influence female distribution. Although the variables that influence the distribution of territorial males have implications for mating opportunities and reproductive success, these relationships remain largely unknown. We assessed how bottom-up, top-down and social factors influence the spatial distribution of territorial male guanacos (Lama guanicoe) in a semiarid ecosystem during three periods of the reproductive season, in a population with two alternative mating tactics: a resource-defence tactic adopted by family group males and a clustered territorial tactic adopted by solitary males. We conducted ground surveys of males from both social units and used density surface models to assess the influence of primary productivity, predation risk and female grouping on their spatial distribution. Our results showed that territorial males were more abundant in areas of increased primary productivity during the group formation period in years of good plant growth and higher number of females/female groups throughout the reproductive season, suggesting that both bottom-up and social traits regulate their spatial distribution. Predation risk did not significantly influence the abundance of territorial males. Overall, our research contributes to the understanding of territorial systems in ungulates and reinforces the current theory that bottom-up processes are relatively more important than top-down processes in regulating populations of large herbivores.